2021
DOI: 10.1021/acsapm.1c00281
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Green Plasticizer on the Performance of Microcrystalline Cellulose/Polylactic Acid Biocomposites

Abstract: In this study, we present the development of eco-friendly biocomposites composed of polylactic acid (PLA) and microcrystalline cellulose (MCC), using melt extrusion and compression molding processes. In all the studied samples, the PLA/MCC ratio was always 1:1, whereas the plasticizer triethyl citrate (TEC) was responsible for the improved dispersion of the MCC in PLA. Tensile tests proved that the developed biocomposites containing TEC show improved ductility and crystallinity, as confirmed by the X-ray diffr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
59
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(69 citation statements)
references
References 68 publications
9
59
0
1
Order By: Relevance
“…These results are in a good agreement with the migration test performed on PLA plasticized with several levulinic acid derivatives, which demonstrated that more polar plasticizers can migrate almost completely out of the PLA in pure water, water containing 10 vol % of ethanol, or 3 wt % of acetic acid . Triethyl citrate (TEC)-plasticized PLA showed similarly high migration into Tenax solid food simulants and the samples containing more than 10 wt % of TEC exceeded the migration limit . The results show that ESOME-plasticized PLA can be used directly for packaging of water and other hydrophilic liquids and foods like fruit juices.…”
Section: Resultsmentioning
confidence: 65%
See 2 more Smart Citations
“…These results are in a good agreement with the migration test performed on PLA plasticized with several levulinic acid derivatives, which demonstrated that more polar plasticizers can migrate almost completely out of the PLA in pure water, water containing 10 vol % of ethanol, or 3 wt % of acetic acid . Triethyl citrate (TEC)-plasticized PLA showed similarly high migration into Tenax solid food simulants and the samples containing more than 10 wt % of TEC exceeded the migration limit . The results show that ESOME-plasticized PLA can be used directly for packaging of water and other hydrophilic liquids and foods like fruit juices.…”
Section: Resultsmentioning
confidence: 65%
“…51 Triethyl citrate (TEC)-plasticized PLA showed similarly high migration into Tenax solid food simulants and the samples containing more than 10 wt % of TEC exceeded the migration limit. 52 The results show that ESOMEplasticized PLA can be used directly for packaging of water and other hydrophilic liquids and foods like fruit juices. Alternatively, it could be aluminized or used in multilayer structures to prevent the migration into solid and lipophilic foods.…”
Section: ■ Results and Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Paul et al [ 168 ] reported the development of PLA/microcrystalline cellulose (MCC) bio composites via melt extrusion and compression molding. Triethylcitrate (TEC) was used as a plasticizer as well as to enhance the dispersion of the microcrystalline cellulose in the PLA matrix.…”
Section: Pla’s Modificationsmentioning
confidence: 99%
“…Results showed improvements in crystallinity and ductility. Results of the mechanical and migration properties suggested that PLA/MCC bio composites with 10 wt.% TEC is the most suitable combination for ecofriendly food packaging applications [ 168 ].…”
Section: Pla’s Modificationsmentioning
confidence: 99%